#TITLE_ALTERNATIVE# - (NIM: 13613013), ADRIAN
The function of an Air Cycle Machine (ACM) is to control the air in the cabin and flight deck of an aircraft to comply the airworthiness requirements with respect to the pressure, oxygen content, and temperature. Due to the importance of ACM, a laboratory instrument is needed to increase studentÃ‚Â’s understanding on the working process of the system. The Aerospace Engineering Study Program of ITB intends to develop an ACM laboratory instrument as a part of the AE3180 Aircraft-Systems lecture activity. This research aims to develop an ACM laboratory instrument as mentioned earlier. The first step is determining the design requirements and objectives of the ACM based on a literature study. The second step is to define the ACM configurations and to select the primary components. The calculation of the air properties in each station of the ACM working process is carried out by using the primary component specifications of the configurations. The final step is to estimate the cost of the primary components for the selected configurations. The research results in two configurations namely the one which uses the Simple Air Cycle (SAC) basis and the other uses a regenerative cooling in the Three Wheel Bootstrap Air Cycle (TWBAC). The calculation results show that the air properties of the two configurations have significant difference of cooling ratio. The Claw Compressor C-DLR 150 60Hz is chosen as the ACM power source and the turbocharger GT0632SZ for the turbine. The targeted output temperature to be less than 10oC has been realized for the selected compressor and for a specific environment condition in Bandung.